Randomized investigation of heart failure therapy in patients with advanced cancer at risk of cardiac wasting: rationale and design of the EMPATICC trial - Anker, Markus; Mahabadi, Amir A.; Totzeck, Matthias; Tewes, Mitra; Mincu, Raluca; Khan, Muhammad Shahzeb; Butler, Javed; Keller, Ulrich; Ahn, Johann; Bullinger, Lars; Modest, Dominik P.; Landmesser, Ulf; et al. (European journal of heart failure, 2025)
End-stage cancer may resemble a heart failure (HF)-like phenotype marked by cardiac wasting, dysfunction, and symptoms such as dyspnoea, congestion, and impaired physical function. The EMPATICC (EMPower the heArt of patients with TermInal Cancer using Cardiac medicines) trial evaluates the safety and efficacy of optimized HF therapy in patients with advanced cancer to improve self-care ability.EMPATICC is a multicentre, investigator-initiated, randomized, double-blind, controlled, proof-of-concept trial employing a joint cardio-oncology care approach. Patients were randomized 1:1 to optimized HF therapy (sacubitril/valsartan, empagliflozin, ivabradine, ferric carboxymaltose) plus usual care, or usual care alone, for 30 days, followed by a 30-day open-label extension. Eligible patients had stage IV solid tumours (per Union for International Cancer Control), were receiving palliative care, had a 1-6 month life expectancy, and were on optimized analgesia. At baseline, first patients had to meet ≥2 criteria of the following indicating cardiovascular risk: heart rate ≥70 bpm, N-terminal pro-B-type natriuretic peptide ≥600 pg/ml, elevated high-sensitivity troponin, left ventricular ejection fraction <55%, left ventricular mass loss >15%, transferrin saturation <20%, or moderate/high likelihood of HF with preserved ejection fraction (based on the HFA-PEFF score); and they had to meet at least one criterion of the following indicating functional limitation: ≥6 s to walk 4 m, inability to wash ≥3 days of the last 7 days, or symptoms of dyspnoea at rest. Enrolment ended 30 January 2025; 93 patients completed randomization. The primary endpoint is a hierarchical composite (analysed by win ratio): (1) days alive and able to wash, (2) 4 m walking ability, and (3) patient global assessment of well-being.EMPATICC evaluates whether HF therapy can improve function and well-being in advanced cancer, potentially reshaping care in this population.
Online veröffentlicht: 26. August 2025
Gesehen am 25.02.2026